CLIL as a transformative approach to teaching practice in the subject of Environmental Management (IGCSE) (2026)
This action plan, framed within action research, aims to address the cognitive challenges faced by eighth and ninth grade students at the Liceo de Colombia Bilingüe (LCB) in their conceptual understanding of the subject Environmental Management (IGCSE) taught in a second language (English). The main challenge is the gap between basic interpersonal communication skills (BICS) and cognitive academic language proficiency (CALP). In this regard, the research contemplates the implementation of the CLIL (Content and Language Integrated Learning) approach as a response to this classroom problem, with a view to contributing to the understanding of scientific knowledge and simultaneously developing language skills (reading, listening comprehension, oral expression, written expression, and technical vocabulary). The study follows a Pedagogical Action Research design with a mixed approach (PIER cycle) to diagnose the situation and propose a CLIL intervention strategy, ensuring that teachers act as agents of change to transform their practices. The data, collected using quantitative (pre/post-tests) and qualitative (diaries and interviews) instruments, will allow for the triangulation of information to measure the impact of CLIL activities on the improvement of academic performance and the development of scientific skills assessed by the IGCSE test, ensuring educational quality and the overall preparation of students.